High Prevalence of Depressive Symptoms Among Ugandan Patients with Rheumatoid Arthritis - Bongomin, Felix; Natukunda, Barbra; Sekimpi, Maria; Olum, Ronald; Baruch Baluku, Joseph; Makhoba, Anthony; Kaddumukasa, Mark (Open Access Rheumatology: Research and Reviews, 2021)
There is a scarcity of data on the burden of depression among Ugandans with rheumatoid arthritis (RA) patients. We aimed to screen for symptoms of depression, their severity and associated factors among patients with RA in Uganda. Patients and Methods: A descriptive, cross-sectional study was conducted between September and December 2020 at Mulago National Referral Hospital (MNRH) and Nsambya Hospital. Patients with RA were enrolled consecutively. Data on demographics, disease course and comorbidities and depression symptomatology were collected through an interviewer administered questionnaire. Symptoms of depression were screened for using the depression/anxiety dimension of the EuroQoL questionnaire. Results: Forty-eight patients with a median age of 52 (IQR: 43.5–60.5) years were recruited in the study. The majority of the patients were female (91.7%, n=44). Twenty-nine patients (60.4%) had comorbidities with a median Charlson comorbidity score of 3 (IQR: 2–4). Overall, 70.8% (n=34) had depressive symptoms. Patients attending MNRH were more likely to have depressive symptoms (p=0.025). Significantly, patients with depressive symptoms were younger (p=0.027), had lower health index value (p<0.001), and lower overall self-reported health status (p=0.013). At binary logistic regression, patients at MNRH (crude odds ratio (COR): 4.32, 95% confidence interval (CI): 1.16–16.15, P=0.030), patients aged <52 years (COR: 5.24, 95% CI: 1.23–22.28, P=0.025) and those with mild RA (COR: 5.71, 95% CI: 1.15–28.35, P=0.033) were significantly more likely to have depressive symptoms. Increase in age (COR: 0.94, 95% CI: 0.89–0.99, P=0.025), and high visual analogue score (COR: 0.94, 95% CI: 0.89–0.99, P=0.013) were protective. Conclusion: Depressive symptoms were common among RA patients in Uganda. Routine screening, diagnosis and management of depression is recommended among young patients to improve quality of life and patient outcomes.
Keywords: Rheumatoid arthritis; Depression; ED-5D-5L